Analisis Keandalan Sistem Informasi Akuntansi Dalam Pengendalian Internal Kas di KSPPS BMT Maslahah Sidogiri - Ahmad Daqiqi; Irfan Fatoni; Endah Puspitosarie; Indah Dewi Nurhayati (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the reliability of the Accounting Information System (AIS) in supporting the effectiveness of internal cash control at KSPPS BMT Maslahah Sidogiri. The research focuses on four key indicators of system reliability: data accuracy, system security, information consistency, and access control, as well as their relationship with internal cash control principles such as segregation of duties, transaction authorization, proper documentation, and regular reconciliation. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observation, and document analysis. Informants included the finance manager, accounting staff, IT personnel, and teller—individuals directly involved in system operations and cash management. The findings indicate that the AIS implemented at BMT Maslahah supports most internal control principles, particularly in transaction authorization and documentation. However, weaknesses were found in information consistency and access control due to insufficient technical training and suboptimal task separation. Thus, the system can be considered reasonably reliable but still requires improvements in several control aspects. These findings are expected to serve as a basis for evaluating and enhancing the accountability and security of cash management within Islamic cooperatives.